Прогнозування тривалої міцності та моделювання процесів повзучості жароміцних матеріалів (за матеріалами наукового повідомлення на засіданні Президії НАН України 21 грудня 2016 року) - Приходько, Р.П. (Вісник НАН України, 2017)
Розроблено новий метод прогнозування тривалої міцності матеріалів, що
ґрунтується на концепції базових діаграм. Запропоновано прості співвідношення, що пов’язують розрахункову довговічність і відповідне їй діюче
напруження, визначене за базовою діаграмою. Ефективність методу проілюстровано при розрахунках довговічності сталей SUS 316-HP (18Cr-12Ni-Mo) і JIS SCMV 4NT (2,25Cr-1Mo) для досить широких діапазонів
діючих напружень і температур. Показано переваги запропонованого підходу порівняно з найпоширенішими параметричними методами Ларсона—Міллера, Орра—Шербі—Дорна, Менсона—Саккопа, Труніна та ін. A method to predict the stress-rupture strength of materials using the master-curve concept is presented. Simple formulas
relating the theoretical lifetime and the corresponding stress determined from the master curve are proposed. To improve
master-function calculations, an assumption is made on linear dependence on the cotangent of the angle between the
ordinate axis and a segment of the stress-rupture curve plotted on log—log scale. The parameters of the linear function
are assumed invariant to the test temperature. The method is capable of extrapolating, with accuracy sufficient for practical purposes, the lifetime to values that are more than two orders of magnitude greater than the available experimental data. The efficiency of the method is illustrated by calculating the lifetime of steels SUS 316-HP (18Cr—12Ni—Mo), and JIS SCMV 4NT (2.25Cr—1Mo) for quite wide ranges of stress and temperature. It is shown that the method has advantages over the master-curve approach and popular parameters such as Larson—Miller, Orr—Sherby—Dorn, Manson—
Succop, Conrad’s, Korchynsky—Clauss, and Trunin’s.